COLORFUL-Circuit: A Platform for Rapid Multigene Assembly, Delivery, and Expression in Plants - Ghareeb, Hassan; Laukamm, Sabine; Lipka, Volker (Frontiers in Plant Science, 2016)
Advancing basic and applied plant research requires the continuous innovative development of the available technology toolbox. Essential components of this toolbox are methods that simplify the assembly, delivery and expression of multiple transgenes of interest. To allow simultaneous and directional multigene assembly on the same plant transformation vector, several strategies based on overlapping sequences or restriction enzymes have recently been developed. However, the assembly of homologous and repetitive DNA sequences can be inefficient and the frequent occurrence of target sequences recognized by commonly used restriction enzymes can be a limiting factor. Here, we noted that recognition sites for the restriction enzyme SfiI are rarely occurring in plant genomes. This fact was exploited to establish a multigene assembly system called “COLORFUL-Circuit”. To this end, we developed a set of binary vectors which provide a flexible and cost efficient cloning platform. The gene expression cassettes in our system are flanked with unique SfiI sites, which allow simultaneous multi-gene cassette assembly in a hosting binary vector. We used COLORFUL-Circuit to transiently and stably express up to four fluorescent organelle markers in addition to a selectable marker and analyzed the impact of assembly design on coexpression efficiency. Finally, we demonstrate the utility of our optimized “COLORFUL-Circuit” system in an exemplary case study, in which we monitored simultaneously the subcellular behavior of multiple organelles in a biotrophic plant-microbe interaction by Confocal Laser Scanning Microscopy.